Exploration of Learning Innovations to Improve Critical Thinking in Student Problem-Solving Through the Design Thinking - Irkhamni, Indika; Nugroho, Aryo Andri; Dwijayanthi, Ida (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
This research aims to understand and analyze the problems experienced by teachers and students in learning mathematics, and explore initial solution ideas based on user needs. The focus of the research is the low critical thinking skills of students and the difficulty in visualizing geometry. This research method uses a qualitative approach with the framework of Design Thinking. Five stages of Design Thinking is (1) empathize, (2) define, (3) ideate, (4) prototype, and (5) test, however this research is limited to ideate stage. Participants consisted of 5 teachers and 98 students from MA Al Utsmani Kajen, MA YMI Wonopringo, and MASS Proto. Data were collected through electronic questionnaires, interviews, and observations using standardized instruments. The exploration results show the need for a problem-based learning model integrated with a gamification approach and supported by Android-based interactive learning media. This research contributes to designing innovative user needs-based solutions that can improve students' critical thinking skills and facilitate the visualization of geometry concepts.